Examining the Association of Economic Instability and Firearm Storage Behaviors - Conrick, Kelsey M; Banks, Samantha; Porter, Sarah F; Rowhani-Rahbar, Ali (American journal of health promotion, 2025)
PurposeTo assess the association between secure firearm storage and economic instability.DesignCross-sectional survey.SettingCalifornia, Minnesota, Nevada, and New Mexico.SampleRespondents to the 2022 and 2023 Behavioral Risk Factor Surveillance System who reported presence of a firearm in or around the home.MeasuresEconomic instability was defined by receipt of food stamps, experiencing threats to shut off utilities, inability to pay bills, employment instability, unreliable transportation, and food insecurity. Firearm storage was dichotomized to "loaded and unlocked" or "all other storage".AnalysisLogistic regression with complex survey weights.ResultsAmong survey respondents who reported a firearm in or around the home (n = 29,977), 25.8% (95% CI: 24.7-26.8%) reported at least one indicator of economic instability, and 17.4% (95% CI: 16.5-18.3%) stored at least one firearm loaded and unlocked. After controlling for age, sex, and the presence of a child in the home, the odds of storing a firearm loaded and unlocked were 1.26 (95% CI 1.07-1.48) times higher for those experiencing economic instability compared to those who were not.ConclusionThese results provide evidence for the association between economic instability and firearm storage behaviors. In promoting secure firearm storage, economic instability may need to be considered as a correlate of that behavior.